Preliminary results of high resolution paleoceanography and paleoclimatology during sapropel S1 deposition (South Limnos Basin, North Aegean Sea). - Kostopoulou, S.; Triantaphyllou, M. B.; Dimiza, M. D.; Gogou, A.; Bouloubassi, I.; Rousakis, G.; Parinos, C.; Diamantopoulou, An.; Geraga, M.; Lykousis, V. (Bulletin of the Geological Society of Greece, 2013)
The paleoenviromental conditions during the depositional interval of sapropel S1 in the northeastern Aegean (gravity core M-4, length 2.53 m; south Limnos basin) are studied based on quantitative micropaleontological (benthic and planktonic foraminifera) and geochemical (OC, δ13Corg) analyses. Special feature of core M-4 is the thickness of S1 layer (96 cm). Our study points that sapropelic layer S1a has been deposited in more dysoxic and warmer conditions in respect to S1b. Both primary productivity and preservation of organic material are more intense during the lower part of S1. An interruption of the sapropelic conditions at 8.0 Ka BP which is mainly characterized by the increase of agglutinated foraminiferal forms confirms both higher oxygen bottom conditions and freshwater input.